Depression in children with hemophilic arthropathy and poliomyelitis: a preliminary report - Çeliker, Reyhan; Gökçe Kutsal, Yeşim; Öy, Belma; Onur, Özlem; Gürgey, Aytemiz (The Turkish Journal of Pediatrics, 2000)
The aim of this study was to evaluate children with chronic disorders like hemophilia and poliomyelitis from the psychological perspective, to determine the frequency of depression, to identify the risk factors and to investigate the relation between disability and depression. Thirty-five patients with disability due to poliomyelitis and 12 patients with hemophilic arthropathy were included in the study. Thirty-six healthy children from the district schools served as controls. The Children's Depression Inventory (CDI) was used to assess the extent of depression. For the hemophilia group, joint scores proposed by the World Federation of Hemophilia were used to assess the degree of joint involvement. The pliomyelitis group was evaluated according to the level of ambulation and the need for orthoses. The CDI score was 10.57 ± 5.87 in the poliomyelitis group, 11.00 ± 5.64 in the hemophilic arthropathy group and 8.39 ± 3.78 in the control group, but the difference was not statistically significant. Four of 35 patients with poliomyelitis (11.4%) and two of 12 hemophilic arthropathy patients (16%) exhibitea depression. None of the children in the control group had depression. Since depression interferes with both medical compliance and rehabilitation potential, early diagnosis and treatment is important. Therefore, evaluation of the pyschological status of chronically ill children must be a part of the rehabilitation program.
Keywords: depression; hemophilia; poliomyelitis